y+15=-3y-9

Simple and best practice solution for y+15=-3y-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+15=-3y-9 equation:


Simplifying
y + 15 = -3y + -9

Reorder the terms:
15 + y = -3y + -9

Reorder the terms:
15 + y = -9 + -3y

Solving
15 + y = -9 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
15 + y + 3y = -9 + -3y + 3y

Combine like terms: y + 3y = 4y
15 + 4y = -9 + -3y + 3y

Combine like terms: -3y + 3y = 0
15 + 4y = -9 + 0
15 + 4y = -9

Add '-15' to each side of the equation.
15 + -15 + 4y = -9 + -15

Combine like terms: 15 + -15 = 0
0 + 4y = -9 + -15
4y = -9 + -15

Combine like terms: -9 + -15 = -24
4y = -24

Divide each side by '4'.
y = -6

Simplifying
y = -6

See similar equations:

| qx+rx=s | | N-10+5n+6=32 | | 182x-0.02x^2+18000=0 | | 44-10n=6(-3n+2) | | 6+3y=15 | | 24=4*w*2 | | -10+8p+1+10p=9 | | -t*6=-7*8 | | (b+9)(b-12)=0 | | 5t+5=7t-4 | | -4-7+1= | | 6x^2-30x+11=0 | | -287=7(1+7n) | | 5y-2(y-6)=43 | | 24=4*w*3 | | -2=6a-4 | | 12x-7=24x+2 | | 2*56=-4 | | 2/5(25)-8=1/5(25)+7 | | 120w-23w=691 | | 1.25-0.3k+.5=1.3+0.5k | | 12x=11x-23 | | P-4+6+7p=74 | | 120w+23w=691 | | (-4-7)+1= | | b/13-3b/13=8/3 | | -16+18=-2(x+6) | | -4=-1-3 | | .5(4x+14)=2(2x-7) | | 125c^2-180= | | .4y+6=31 | | 0.5x-0.75y=-2 |

Equations solver categories